Effect of anti-solar glass film on heat transfer and mean radiant temperature inside cabin of air-conditioned vehicle - Srisilpsophon T. (2014)
This paper addresses solar heat load entering an air-conditioned pickup-car cabin and behaviour of the mean radiant temperature, MRT, in the cabin including the fuel consumption due to the air conditioner. The experiments have been carried out under the climate of Bangkok, Thailand when all the windows except the windscreen are coated with 40% cutoff anti-solar film. A set of mathematical models to evaluate the surface temperatures of the windows and the cabin walls has been presented and the results agree quite well with those of the experimental data. With the temperatures inside the car cabin, the MRT could be calculated. It was found that with the film coating on the windows, the MRT inside the cabin comes closer to the inside air temperature than without the film. For films of 40, 60 and 80% radiation cutoff, when the outside air temperature is lower than 25°C, the lighter film gives similar performance to the darker film. When the outside temperature is higher than 25°C, the darker film shows an advantage in reducing the MRT. In a car with 40, 60 and 80% cutoff anti-solar film the cooling load could be reduced by about 14, 18 and 20%, respectively, compared with that without the film. Fuel savings could be about 11.7, 14.4 and 18%, respectively. © Ambient Press Limited 2007.